Childhood invasive pneumococcal disease: a hospital-based study from Malaysia - Lim, L.H.; Lee, Way Seah; Parasakthi, N. (Wiley, 2007)
Aim: New conjugate vaccine for Streptococcus pneumoniae has been introduced in Malaysia recently. Information on infection due to S. pneumoniae in Malaysian children is scarce. We conducted a retrospective chart review of childhood invasive pneumococcal disease (IPD) presented to a single centre in Malaysia. Methods: A retrospective review of 5 years and 4 months of all cases of IPD in children younger than 14 years of age (May 1999-August 2004) seen at the University of Malaya Medical Centre (UMMC), Kuala Lumpur, was conducted. Cases were identified from the record of Department of Medical Microbiology, UMMC. Results: IPD was identified in 50 children (median age 1.1 years, range 2 weeks-14 years) during the study period. Seventy-six per cent of the cases were younger than 2 years of age. Pattern of infections noted include definite pneumonia (n = 8), probable pneumonia (n = 33), meningitis (n = 4), bacteraemia without focus (n = 4) and septic arthritis (n = 1 each). Pre-morbid diseases were present in 28 of all cases. Complications (n = 12, 24) due to IPD were seizures (n = 5), pleural effusion/empyema (n = 4), cerebral palsy (n = 2) and deafness (n = 1). No deaths were attributed to IPD. Sixty-two per cent of the pneumococcal isolates were penicillin non-susceptible and were detected throughout the study period. Conclusions: IPD is associated with high morbidity, particularly among young children. Majority of the isolates were penicillin-non-susceptible strains. Additional information on the serotype of S. pneumoniae isolated is necessary to assess the potential impact of immunisation on preventing pneumococcal infection in Malaysia.